Different Surfactants-Engineered Cofe2o4 Nanoparticles: A Multifunctional Platform for Magnetic Hyperthermia and Wastewater Purification Applications - Radhalayam, D (ELSEVIER, 2026)
Biomedical and photocatalytic properties of many spinel ferrites nanoparticles were evaluated for variety of applications in healthcare and sustainable environment fields. Well crystallined, narrow size distributed magnetically anisotropic CoFe2O4 nanoparticles (NPs) were synthesized by solvothermal reflux method. Both hydrophobic, long chain oleic acid (OA) dispersant ligated CoFe2O4 NPs (CoFe2O4-OA), and hydrophilic, short chain zwitterionic dopamine sulfonate (ZDS) dispersant ligated CoFe2O4 NPs (CoFe2O4-ZDS) were made, and studies their magnetic heating capacities, cytotoxicity, and photocatalytic properties at difference concentration of NPs. All the standard analytical tools were used to characterize the aimed properties. Magnetic heating properties of NPs were studied under 408 & 455 Oe, and 316 kHz alternate magnetic field. Among the 12 samples studied, CoFe2O4-ZDS NPs in water show highest 568 W/g, and CoFe2O4-OA NPs in hexane show highest 260 W/g at 0.5 mg/mL under 455 Oe & 316 kHz magnetic field. Heating capacity decreases with increase of NPs concentration due to magnetic dipole interactions and decrease of Brown magnetic moment relaxation time. MTT assay cytotoxicity results show that ZDS ligated NPs are relatively good cytocompatible with HEK293 normal and MCF-7 carcinoma cell lines than OA ligated NPs. Similarly, CoFe2O4-ZDS NPs show high rhodamine B dye degradation in water (97.5 %) than CoFe2O4-OA NPs under UV light (254 nm). The results suggest that CoFe2O4ZDS NPs are considered for magnetic hyperthermia and dye degradation applications.
Keywords: Magnetic hyperthermia; Cobalt ferrite; Superparamagnetic nanoparticles; Cytotoxicity; Dye degradation